Kesiapan Penerapan Pembelajaran Aktif, Kreatif dan Menyenangkan bagi Anak Usia Dini di Era New Normal - Waode Eti Hardiyanti; Sulkifly Sulkifly; Jumadi Mori Salam Tuasikal (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2021)
In order to organize learning during the new normal era, due to the COVID-19 outbreak, various suitable strategies are needed in order to create active, creative, and fun learning. Therefore, this study aims to determine the readiness of Early Childhood educators in conducting face-to-face learning (PTM) in the new academic year 2021/2022. A total of ten teachers and staff were invited to conduct interviews and fill out a questionnaire related to face-to-face learning. The results show that as many as the majority of teachers and staff are ready to welcome face-to-face learning which will start in the new academic year 2021/2022, as many as 9 out of 10 stated their readiness. This readiness is inseparable from the availability of facilities and infrastructure that are adapted according to health protocols and also the readiness of teacher competencies in preparing various media, strategies, activities and games to facilitate learning both synchronously and asynchronously.